Tailoring of boron-doped MnTe semiconductor-sensitized TiO2 photoelectrodes as near-infrared solar cell devices - Auttasit Tubtimtae (2018)
We studied the photovoltaic performance of a new tailoring of boron-doped MnTe semiconductor-sensitized solar cells (B-doped MnTe SSCs). The B-doped MnTe semiconductor was grown on TiO 2 using two-stages of the successive ionic layer adsorption and reaction (SILAR) technique as a photoelectrode. The phase of the boron-doped MnTe and MnTe 2 semiconductor as sensitizers were characterized with ∼20-50 nm in diameter. The B-doped MnTe(5) exhibited the best efficiency of 0.04%, compared to that of the undoped sample of 0.006%. In addition, the band gaps of 1.30 and 1.26 eV were determined for the undoped and B-doped MnTe NP s, respectively. The change in the band gap after boron doping was performed due to crystal quality improvement and the larger size of the MnTe NPs, leading to a broader absorption of the sensitizer and a noticeable improvement in the photovoltaic performance. This kind of semiconductor and synthesis procedure can be applied for further improvement in a higher efficiency and more stability in SSCs. © 2013 Published by Elsevier Ltd. All rights reserved.